Imide-yne click polymerization: a new and versatile tool for the toolbox of X-yne click polymerization - ÇAKMAKÇI, EMRAH (My University, 2024)
The Michael reaction, a cornerstone in organic chemistry, continues to revolutionize the field with its unparalleled versatility in forming carbon-carbon, carbon-oxygen, carbon-nitrogen, and carbon-sulfur bonds, paving the way for groundbreaking advancements in complex molecule and macromolecule construction. In this study, imide-yne reaction was employed at the macromolecular level for the first time to prepare linear poly(imide ester)s. A wide range of bisimides and dipropiolates were reacted through imide-yne click polymerization in the presence of 1,4-diazabicyclo[2.2.2] octane (DABCO) at room temperature. The polymerizations proceed in an anti-Markovnikov fashion, yielding the E-isomer as the major product. Polymers were obtained in high yields and their molecular weights were found to be in the range of 5.64-12.67 kDa. The remaining unreacted double bonds in the linear polymers were found to undergo further functionalization with thiols using a strong organocatalyst 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), which was also supported by a model study. Post-polymerization modification study prompted us to prepare imide-yne monomers that can react with dithiols to synthesize poly(imide thioether)s through nucleophilic thiol-ene click reaction using TBD as the catalyst. The obtained polymers displayed a wide range of glass transition temperatures and thermal stability. Thus, it can be said that the proposed method enables the synthesis of new polyimide-based structures with tailorable thermal properties. It is believed that the proposed strategy will make a significant contribution to expanding the versatility of active alkyne chemistry at the macromolecular level.
Keywords: Biyomedikal Mühendisliği; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik Bilişim Ve Teknoloji (Eng); Temel Bilimler (Sci); Yaşam Bilimleri (Life); Mühendislik; Moleküler Biyoloji Ve Genetik; Mühendislik Biyomedikal; Polimer Bilimi; Kimya Organik; Biyokimya Ve Moleküler Biyoloji; Engineering Computing & Technology (Eng); Natural Sciences (Sci); Life Sciences (Life); Engineering; Molecular Biology & Genetics; Engineering Biomedical; Polymer Science; Chemistry Organic; Biochemistry & Molecular Biology; Biyomühendislik; Fizik Bilimleri; Polimerler ve Plastikler; Organik Kimya; Bioengineering; Physical Sciences; Polymers and Plastics; Organic Chemistry